Alginate/gelatine hydrogels: characterisation and application of antioxidant release. Issue 4 (12th October 2017) - Nooeaid, Patcharakamon; Chuysinuan, Piyachat; Techasakul, Supanna
Abstract : Green polymer-based hydrogels have been broadly applied in the pharmaceutical, medical, food and agricultural industries. Alginate/gelatine blended hydrogels loaded with guava leaf extract were prepared using the simple physical crosslinking in situ gelation method. Different blending ratios were investigated in terms of the physico-chemical properties of the hydrogels including morphology, chemical composition, mechanical properties, water absorption and release behaviour. Results indicated that gelatine content had a positive effect on loading capacity and encapsulation efficiency. Increasing gelatine content in the blends significantly improved tensile properties, particularly elongation at fracture, while the ability of the hydrogels to absorb water decreased with increasing gelatine quantity. Extract-loaded hydrogels expressed high antioxidant activity, reaching approximately 70% 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging after 30 min immersion in saline solution. Extract release from the hydrogels was controlled by swelling and polymer relaxation mechanisms according to the Korsmeyer–Peppas kinetic model. Results suggested that antioxidant-loaded alginate/gelatine hydrogels are of interest for biomedical applications.